Manifestations of Natural Written Speech: Inscriptions on Photos - N. A. Krasovskaya (Дискурс профессиональной коммуникации, 2021)
The main purpose of this article is to dwell on the consideration of some genres of natural writing. The very concept of “natural written speech” at the present time has not received a complete and comprehensive interpretation. However, recently we have come across its existence much less often. In part, the disappearance of the genres of natural writing is associated with the onset of the digital era, when people stopped writing letters to each other on paper, notes, making notes for themselves, stopped signing photographs. Many genres of writing are capable of giving an idea of the writer in the same way as varieties of oral speech. In natural written speech, some personality traits and linguistic personality are manifested. The aim of the research, presented in the article, is to analyze inscriptions on photographs from the viewpoint of their lexis, punctuation, graphical layout to define the chronotope and personal characteristics of the author, who produces this genre of written discourse. The focus is on the linguistic means of inscriptions on photos, i.e. graphic, lexical, derivational and some others. In the process of analyzing such a genre of writing as inscriptions on photographs, the main varieties of this genre were identified: inscriptions made as a memento, inscriptions that represent the definition of an event or time and place; inscriptions made to convey information to close relatives, etc. In addition, the inscriptions on photographs can be classified by keywords, if possible, determining the chronotope, by the use of graphic means, by the location of the inscription itself in the photograph. To a certain extent, the inscriptions made on photographs reflect the personality traits of a person. The analysis shows, that the inscriptions on photographs have become somewhat of a harbinger of personal pages on Instagram.